GATS tag system is compatible with biotin labelling methods for protein analysis - Kohdai Yamada; Fumiya Soga; Soh Tokunaga; Hikaru Nagaoka; Tatsuhiko Ozawa; Hiroyuki Kishi; Eizo Takashima; Tatsuya Sawasaki (Scientific Reports, 2023)
Abstract Polypeptide tags and biotin labelling technologies are widely used for protein analyses in biochemistry and cell biology. However, many peptide tag epitopes contain lysine residues (or amino acids) that are masked after biotinylation. Here, we propose the GATS tag system without a lysine residue and with high sensitivity and low non-specific binding using a rabbit monoclonal antibody against Plasmodium falciparum glycosylphosphatidylinositol (GPI)-anchored micronemal antigen (PfGAMA). From 14 monoclonal clones, an Ra3 clone was selected as it recognized an epitope—TLSVGVQNTF—without a lysine residue; this antibody and epitope tag set was called the GATS tag system. Surface plasmon resonance analysis showed that the tag system had a high affinity of 8.71 × 10–9 M. GATS tag indicated a very low background with remarkably high sensitivity and specificity in immunoblotting using the lysates of mammalian cells. It also showed a high sensitivity for immunoprecipitation and immunostaining of cultured human cells. The tag system was highly sensitive in both biotin labelling methods for proteins using NHS-Sulfo-biotin and BioID (proximity-dependent biotin identification) in the human cells, as opposed to a commercially available tag system having lysine residues, which showed reduced sensitivity. These results showed that the GATS tag system is suitable for methods such as BioID involving labelling lysine residues.